2018
DOI: 10.1021/acs.jpcb.8b07409
|View full text |Cite
|
Sign up to set email alerts
|

The Sensitivity of Computational Protein Folding to Contact Map Perturbations: The Case of Ubiquitin Folding and Function

Abstract: Ubiquitin is a small model protein, commonly used in protein folding experiments and simulations. We simulated ubiquitin using a well-tested structure-based model coarse-grained to a C α level (C α -SBM) and found that the simulated folding route did not agree with the experimentally observed one. Simulating the C α -SBM with a cutoff contact map, instead of a screened contact map, switched the folding route with the new route matching the experimental route. Thus, the simulated folding of ubiquitin is sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 75 publications
(196 reference statements)
2
6
0
Order By: Relevance
“…Several single-domain globular proteins similar in size to the CP monomer fold cooperatively, , that is, only two equi-free-energetic basins (folded and unfolded) are populated at T f with a barrier separating them. However, simulations of CP (Figure A) showed that a single partially folded basin (Figure C), whose position shifted with simulation temperature (Figure S1), was populated.…”
Section: Resultsmentioning
confidence: 99%
“…Several single-domain globular proteins similar in size to the CP monomer fold cooperatively, , that is, only two equi-free-energetic basins (folded and unfolded) are populated at T f with a barrier separating them. However, simulations of CP (Figure A) showed that a single partially folded basin (Figure C), whose position shifted with simulation temperature (Figure S1), was populated.…”
Section: Resultsmentioning
confidence: 99%
“…The criteria used to generate the contact map have been known to influence the folding pathway. 43 The native state contact map was generated for the crystal structure of apo CAP stored in PDB ID 3FWE (Figure 1), after mutating the leucine at position 138 to aspartic acid using VMD. The structure of wild type apo CAP (3HIF) was not chosen because of its lower resolution and missing electron density for the important hinge region residues.…”
Section: Methodsmentioning
confidence: 99%
“…The geometric occlusion criteria consider all residues (only Cα atoms in this case) within a cutoff distance of 6 Å to be in contact and then removes any contact which is geometrically obstructed (where atoms are interacting via intervening atoms). The criteria used to generate the contact map have been known to influence the folding pathway . The native state contact map was generated for the crystal structure of apo CAP stored in PDB ID 3FWE (Figure ), after mutating the leucine at position 138 to aspartic acid using VMD.…”
Section: Methodsmentioning
confidence: 99%
“…Different flavors of Gō models have been tested on a few proteins, and for the most part, as long as little to no frustration in the form of nonnative interactions is encoded, diverse features of protein folding calculated from the different models are both similar to each other and to experimental results (15,60,61). However, functional regions of proteins can be either energetically or topologically frustrated, and in such cases, different unfrustrated Gō models can give different folding features (62,63), and energetic frustration in the form of nonnative interactions ( Fig. 2) needs to be explicitly included in the model (54, 64 -66).…”
Section: Encoding Structure In Gō Modelsmentioning
confidence: 99%